Three-Dimensional Reconstructed Bone Marrow Matrix Culture Improves the Viability of Primary Myeloma Cells In-Vitro via a STAT3-Dependent Mechanism - Yung-Hsing Huang; Meaad Almowaled; Jing Li; Christopher Venner; Irwindeep Sandhu; Anthea Peters; Afsaneh Lavasanifar; Raymond Lai (Current Issues in Molecular Biology, 2021)
Primary myeloma (PM) cells are short-lived in conventional culture, which limited their usefulness as a study model. Here, we evaluated if three-dimensional (3D) culture can significantly prolong the longevity of PM cells in-vitro. We employed a previously established 3D model for culture of bone marrow mononuclear cells isolated from 15 patients. We assessed the proportion of PM cells, viability and proliferation using CD38 staining, trypan blue exclusion assays and carboxy fluorescein succinimidyl ester (CFSE) staining, respectively. We observed significantly more CD38+ viable cells in 3D than in conventional culture (65% vs. 25%, p = 0.006) on day 3. CFSE staining showed no significant difference in cell proliferation between the two culture systems. Moreover, we found that PM cells in 3D culture are more STAT3 active by measure of pSTAT3 staining (66% vs. 10%, p = 0.008). Treatment of IL6, a STAT3 activator significantly increased CD38+ cell viability (41% to 68%, p = 0.021). In comparison, inhibition of STAT3 with Stattic significantly decreased PM cell viability in 3D culture (38% to 17% p = 0.010). Neither IL6 nor Stattic affected the PM cell viability in conventional culture. This study suggests that 3D culture can significantly improve the longevity of PM cells in-vitro, and STAT3 activation can further improve their viability.